Moral panics in social media times: Disinformation and panic about what others say and read on the internet - Aguerri, Jesús; Gatti, Carlo; Jiménez, Aitor (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2025)
This article aims to demonstrate that the concept of moral panic and its associated theoretical construction are of crucial importance in understanding how the media convey information and fabricate social problems in contemporary society. To illustrate this argument, we examine the social concern surrounding disinformation, which also enables us to display how the fear thereof thrives on social anxiety about the consequences of online speech acts. Our contention is that within the current communicative landscape, influenced by digitalisation and the centrality of social networks, the media continually produce—albeit not always explicitly—images and discourses about deviance that are designed to provoke responses of outrage and moral panic among the public. This ongoing competition for ‘panic production’ evolves into a struggle to control daily trends and, paradoxically, may impede the emergence of significant and successful moral panics akin to those described by Cohen. Nevertheless, these potential and ‘short-range’ panics coalesce around social anxieties and fears, reinforcing them and perpetually laying the groundwork for new panics to arise.